Decarnivering. En analyse av Guds lam, steken og kosedyret - Døving, Runar (Tidsskrift for kulturforskning, 2011)
The sheep provides man with meat, and also the form for cuddly lamb toys. How does this transformation take place, i.e. from animal to food and toy? It seems that the animal must go through a reification process for it to become food, and that this process happens simultaneously with an extensive nostalgic idyllisation of agriculture. This article takes text sources as its point of departure, primarily the Bible; it will focus on the production of lambs for meat, and the production of cuddly toy lambs, as being two opposing processes. In the former process, the process of "deanimation", the "animal is removed from the meat" in order for it to become food; in the latter process, the process of "decarnalisation", the meat is "removed" from the animal and transformed into an anthropomorphic idyllised being to become a cuddly toy. However, it seems as if modern urban man is not completely able to distance himself from the animal, or the holy relationship between the sheep and man as expressed in western cultural history. In contrast to the public ritual slaughter of the animal as practiced by the Jews in the Old Testament, the modern secular state "conceals" the slaughter of the animal for food production from the public. The slaughter of the animal is taken over by seemingly instrumental meat processing companies, such as the Norwegian company Gilde, which in turn lets "the role of God" be taken on by the Norwegian Food Safety Authority (Mattilsynet), which functions as a witness of everything being carried out the right way. The article argues that although the slaughter (and "sacrifice") of the animal has let out of view of the public in the modern secular Norwegian state, considerable ambivalence still surrounds the commoditisation of the sheep.